The Effect of Imprintweb Series Advertising on Consumer Trust and Purchase Interest in Makassar City - La Ode Alfian Friz; Fitriana Fitriana (Pascasarjana STIE Amkop Makassar, 2021)
AbstractThe study was conducted in Makassar City with the population these are consumers who have watched web series advertisements and bought the product. The study sample was 234 respondents, to analyze the data by using a structural equation modeling (SEM) program with analysis tools using Smart PLS 3.0. The outcomes of the study show that: (1) Taste-print web series ads have a significant impact on trust. This shows that web series ads used in promoting products can rise consumer buying interest, (2) Web series ads have a significant impact on buying interest, the more people who watch the ad, the higher the consumer's buying interest, (3) trust has a significant impact on buying interest, this shows the higher consumer confidence after watching the web series advertisement the taste trail is the higher the consumer's desire to buy the product, (4) the trail web series advertisement taste has an indirect and significant effect on buying interest through trust, this shows that the higher the flavor trail web series ads applied by marketers will create buying interest through trust. Kata Kunci: Web series Advertising, Trust, buying interest